Histone deacetylase inhibitors are potent inducers of gene expression in latent EBV and sensitize lymphoma cells to nucleoside antiviral agents - Ghosh, Sajal K. (American Society of Hematology, 2012)
Induction of EBV lytic-phase gene expression, combined with exposure to an antiherpes viral drug, represents a promising targeted therapeutic approach to EBV-associated lymphomas. Short-chain fatty acids or certain chemotherapeutics have been used to induce EBV lytic-phase gene expression in cultured cells and mouse models, but these studies generally have not translated into clinical application. The recent success of a clinical trial with the pan-histone deacetylase (pan-HDAC) inhibitor arginine butyrate and the antiherpes viral drug ganciclovir in the treatment of EBV lymphomas prompted us to investigate the potential of several HDAC inhibitors, including some new, highly potent compounds, to sensitize EBV(+) human lymphoma cells to antiviral agents in vitro. Our study included short-chain fatty acids (sodium butyrate and valproic acid); hydroxamic acids (oxamflatin, Scriptaid, suberoyl anilide hydroxamic acid, panobinostat [LBH589], and belinostat [PXD101]); the benzamide MS275; the cyclic tetrapeptide apicidin; and the recently discovered HDAC inhibitor largazole. With the exception of suberoyl anilide hydroxamic acid and PXD101, all of the other HDAC inhibitors effectively sensitized EBV(+) lymphoma cells to ganciclovir. LBH589, MS275, and largazole were effective at nanomolar concentrations and were 10(4) to 10(5) times more potent than butyrate. The effectiveness and potency of these HDAC inhibitors make them potentially applicable as sensitizers to antivirals for the treatment of EBV-associated lymphomas.